2021
DOI: 10.3390/jcm10173891
|View full text |Cite
|
Sign up to set email alerts
|

Association between Early Absolute Neutrophil Count and Level of D-Dimer among Patients with COVID-19 Infection in Central Taiwan

Abstract: Thromboembolism is a critical event in patients with coronavirus disease (COVID)-19 infection and highly associated with neutrophil extracellular traps. D-dimer has been found to be an essential thromboembolism-associated biomarker; however, the association between absolute neutrophil count (ANC) and level of D-dimer in patients with COVID-19 infection remains unclear. In this study, we enrolled consecutive patients with COVID-19 admitted to Taichung Veterans General Hospital (TCVGH), a referral center in cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Studying neutrophil activation markers shows that they could help identify non-critical patients under an increased risk of developing the critical form of the disease [ 37 ]. In line with the previous results from a recent Taiwanese study [ 38 ], we observed significant correlations between D-Dimer concentration and the need for mechanical ventilation, both invasive or non-invasive, amongst our patients. Of all the patients included in the study, 105 (70%) required invasive ventilation, 100 (95%) of whom have died.…”
Section: Discussionsupporting
confidence: 93%
“…Studying neutrophil activation markers shows that they could help identify non-critical patients under an increased risk of developing the critical form of the disease [ 37 ]. In line with the previous results from a recent Taiwanese study [ 38 ], we observed significant correlations between D-Dimer concentration and the need for mechanical ventilation, both invasive or non-invasive, amongst our patients. Of all the patients included in the study, 105 (70%) required invasive ventilation, 100 (95%) of whom have died.…”
Section: Discussionsupporting
confidence: 93%
“…Although white blood cells only account for 0.2% of whole blood, they play an important role in protecting human health [1]. White blood cells are generally divided into neutrophils, eosinophils, basophils, monocytes, and lymphocytes [2], and changes in these cell counts can be used as the basis for diagnosing certain diseases or evaluating the therapeutic efect of certain diseases [3][4][5][6][7][8][9]. Terefore, the accuracy and efciency of white blood cell detection and classifcation are very important for the auxiliary diagnosis of diseases [10].…”
Section: Introductionmentioning
confidence: 99%